AN ANALYSIS ON PEDAGOGY CONTENT ISLAMIC KNOWLEDGE OF INDONESIAN QUALIFICATION FRAMEWORK IN BIOLOGY ISLAMIC EDUCATION PROGRAM - Herlanti, Yanti (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2017)
Abstract This study aims to analyze Pedagogy Content Islamic Knowledge (PCIK) on the Indonesian Qualification Framework (IQF) in Biology Islamic Education Study Program. The competence in Pedagogy Content Knowledge (PCK) is the achievement of Biology Education Program. The challenge faced by Biology Islamic Education program which lies under Islamic colleges and universities is to combine the program with the knowledge of Islam. The graduates of Biology Islamic Education program are required to master the Pedagogy Content Islamic Knowledge (PCIK). PCIK analysis was conducted qualitatively on Biology Islamic Education curriculum document at three state Islamic universities in Indonesia. The subjects of the study were three heads of study program, fourteen lecturers, and sixteen students. In-depth interviews, questionnaires, and discussions were conducted on the subjects. The results showed that PCIK is conceptually and textually seen in three subjects, namely capita selecta, microteaching practice, and school field practice. PCIK appeared in the scientific process, i.e. critical reflective activity on the significance of natural phenomena created by God. Abstrak Penelitian ini bertujuan untuk menganalisis Pedagogy Content Islamic Knowledge (PCIK) pada Kerangka Kualifikasi Nasional Indonesia (KKNI) Program Studi Tadris Biologi. Kemampuan Pedagogy Content Knowledge (PCK) merupakan capaian Program Studi Pendidikan Biologi. Bagi program studi Tadris Biologi di bawah naungan PTKI (Perguruan Tinggi Keagamaan Islam) memiliki tantangan satu tantangan lagi yaitu memadukan dengan pengetahuan islam. Keluaran dari Tadris Biologi dituntut kemampuan Pedagogy Content Islamic Knowledge (PCIK). Analisis PCIK dilakukan secara kualitatif terhadap dokumen kurikulum Tadris Biologi pada tiga UIN di Indonesia. Selain itu dilakukan wawancara mendalam, pengisian angket, dan diskusi terpumpun bersama narasumber yaitu tiga orang ketua program studi, empat belas dosen, dan enam belas mahasiswa. Hasil penelitian menunjukkan PCIK secara tekstual konseptual terlihat pada tiga matakuliah yaitu kapita selekta, praktik pengajaran mikro, dan praktik lapangan madrasah. PCIK muncul pada proses sains berupa kegiatan reflektif kritis terhadap hakekat fenomena alam yang diciptakan oleh Alloh swt. How to Cite : Herlanti, Y. (2017). An Analysis on Pedagogy Content Islamic Knowledge of Indonesian Qualification Framework in Biology Islamic Education Program. TARBIYA: Journal of Education in Muslim Society, 4(2), 176-183. doi:10.15408/tjems.v4i2.6751. Permalink/DOI: http://dx.doi.org/10.15408/tjems.v4i2.6751